The Teacher as a Model of Life and Thought - Michele De Beni (Nicolaus Copernicus University in Toruń, 2019)
The present article focuses on pedagogical aspects emerging from Chiara Lubich's written work and oral conversations. Here, three major points are elaborated: the importance of the relationship as a fundamental element of education; the importance of the educational model, conceptualised as the need of an Ideal Teacher source of life inspiration; the concept of thought and knowledge as a service of love to the world. Points of conversation were fostered within the framework of these aspects to develop a model upon which education, thought and action are built as means of fraternal service.